Interactive effects of atmospheric oxidative pollutants and heat on circulatory disease mortality - Wang, Wenli; Chen, Yang; Li, Ruoyu; Yang, Linsheng; Jiang, Yu; Xiang, Jianjun; Wu, Jing; Li, Jing; Liu, Baoying; Lin, Huaying; Wu, Chuancheng (Frontiers in Public Health, 2025)
BackgroundAtmospheric oxidative pollutants, air temperature, and heatwave events pose potential threats to public health. However, the combined effects of these factors on the risk of mortality from circulatory disease remain insufficiently studied. This study aims to evaluate the synergistic effects of ozone (O₃), oxidant (Ox), and nitrogen dioxide (NO₂) with temperature and heat waves, and to explore their impact on circulatory disease mortality, providing evidence to support public health interventions.MethodsBased on the mortality, meteorological, and environmental protection data of residents in Fuzhou City from January 1, 2016, to December 31, 2022, we employed a generalized additive model (GAM) and a distributed lag nonlinear model (DLNM) to assess the effects of atmospheric oxidative pollutants interacting with temperature and heat waves on the risk of death from circulatory diseases, where temperature includes the daily maximum temperature and diurnal temperature range (DTR). A bivariate three-dimensional model was used to visualize their synergistic effects, and stratified analyses were conducted to compare differences between heat wave and non-heat wave periods.ResultsO3, Ox, and NO2 exhibit synergistic effects with ambient temperature, and their combined exposure significantly increases the mortality risk of circulatory system diseases, myocardial infarction, and stroke, with some health effects showing a “nonlinear exposure-response relationship with an inverted U-shaped pattern.” Under heatwave conditions, the synergistic effect between NO2 and high temperatures is markedly enhanced, leading to a greater increase in mortality risk compared to O3 and Ox, and demonstrating both a same-day lag and a cumulative effect. After introducing other pollutants into the dual-pollution model, NO2 still shows a strong independent health effect on major causes of death during heatwaves, with the most pronounced risk elevation observed for stroke.ConclusionAtmospheric oxidative pollutants interact with high temperatures, diurnal temperature range, and heatwaves, significantly increasing the risk of mortality. It is essential to integrate air pollution and meteorological factors to strengthen health protection during high-risk periods.